Elevated catalase expression in a fungal pathogen is a double-edged sword of iron - Pradhan, Arnab (PLoS Pathog, 2017)
Most fungal pathogens of humans display robust protective oxidative stress responses that contribute to their pathogenicity. The induction of enzymes that detoxify reactive oxygen species (ROS) is an essential component of these responses. We showed previously that ectopic expression of the heme-containing catalase enzyme in Candida albicans enhances resistance to oxidative stress, combinatorial oxidative plus cationic stress, and phagocytic killing. Clearly ectopic catalase expression confers fitness advantages in the presence of stress, and therefore in this study we tested whether it enhances fitness in the absence of stress. We addressed this using a set of congenic barcoded C. albicans strains that include doxycycline-conditional tetON-CAT1 expressors. We show that high basal catalase levels, rather than CAT1 induction following stress imposition, reduce ROS accumulation and cell death, thereby promoting resistance to acute peroxide or combinatorial stress. This conclusion is reinforced by our analyses of phenotypically diverse clinical isolates and the impact of stochastic variation in catalase expression upon stress resistance in genetically homogeneous C. albicans populations. Accordingly, cat1Δ cells are more sensitive to neutrophil killing. However, we find that catalase inactivation does not attenuate C. albicans virulence in mouse or invertebrate models of systemic candidiasis. Furthermore, our direct comparisons of fitness in vitro using isogenic barcoded CAT1, cat1Δ and tetON-CAT1 strains show that, while ectopic catalase expression confers a fitness advantage during peroxide stress, it confers a fitness defect in the absence of stress. This fitness defect is suppressed by iron supplementation. Also high basal catalase levels induce key iron assimilatory functions (CFL5, FET3, FRP1, FTR1). We conclude that while high basal catalase levels enhance peroxide stress resistance, they place pressure on iron homeostasis through an elevated cellular demand for iron, thereby reducing the fitness of C. albicans in iron-limiting tissues within the host.